Pharmacognostical study of stem and bark of bauhinia vahlii (wight & arn) - sirola, Preeti; Kapil, Kumar; Saxena, Manish Kumar; Sen, Amit Kumar; Himanshu, Lohani; Vaishali, Rajput; A, K.S Rawat (International Journal of Indigenous Herbs and Drugs, 2024)
Bauhinia is known by its medicinal effect in the body system as because it is used in many disease for their initial treatment with no such sevier side effect. This research based on the testing of the plant Bauhinia vahlii and its wide analysis. Plant was collected mainly from threeregions of India Uttarakhand (Pithoragarh, Kathgodam, Gathiya). Stem and Bark part of the plant is taken for research. The research elaborates transverse and longitudinal section of this plant. Research include analysis and testing of the plant with addition of it chromatography by the HPTLC. The complete research done by study of steam and bark of the plant Bauhinia vahlii. The result obtain by the research in the constituents of steam and bark clearly shows all the characterization and positive approach towards the health benefit of it. As traditionally it is seen to usage of its leaf in the covering of some edible sweets like singauri because of its extraordinary pharmaceutical benefits which seems in the result came by this research. This creeper like medicinal plant with structurally wide leaf is widely grows in the hilly areas of Uttarakhand by itself.